Simplified Japanese Self-Perception Scale for Young Adults (SJS-PSYA) to identify risk cases - Reiko, Ueda; Okamura, Jun (Journal of Advanced Nursing, 2001)
Simplified Japanese Self‐Perception Scale for Young Adults (SJS‐PSYA) to identify risk cases Aim. The purpose of this study was to investigate the effectiveness of the newly devised Simplified Japanese Self‐Perception Scale for Young Adults (SJS‐PSYA) for identifying risk cases. The SJS‐PSYA was used to measure self‐perception of young adults and its validity was examined. The subjects were 196 Japanese young adults (91 males, 105 females) who had participated in the longitudinal study of Ueda (1996, 1998) from infancy and preschool years to adolescence. Method. Questionnaires for subjects and their parents were mailed separately and then interviews were conducted for possible risk subjects and their parents. Results. (1) The total score of the SJS‐PSYA was correlated negatively with the total number of risk variables. (2) Eight out of 10 single risk variables were correlated with the total self‐perception score. Better subjective health, higher aspiration for future, employed at present, much satisfaction in life, much support from friends as well as family and higher appraisal of nurturance of own parents, higher was the total self‐perception score. These results suggest that the SJS‐PSYA could be used in identifying young adults at risk and for intervention.